Application of Simultaneous Location and Map Construction Algorithms Based on Lidar in the Intelligent Robot Food Runner. Issue 1 (July 2021) - Cheng, Jia; Liu, Zhendong; He, Jiaxi; Deng, Yuting; Zhang, Hao
Abstract: With the rapid development of artificial intelligence, there are more and more "shadows" of artificial intelligence in restaurants. In the market, the intelligent robot food runner is relatively expensive and not widely used. In this paper, an intelligent robot food runner with lower price but better performance is proposed, which is suitable for restaurants. Among them, this paper mainly analyzes how to use laser radar SLAM to build restaurant map, locate and navigate, and how to build obstacle avoidance and path planning. Through ROS platform, the whole process of intelligent robot food runner is simulated and verified, which can meet the needs of restaurants.